Oxford handbook of international adjudication - Romano,Cesare PR,Ed (OUP, 2014)
The post Cold War proliferation of international adjudicatory bodies and international adjudication has had dramatic effects on both international law and politics, greatly affecting international relations, particularly economic relations, the enforcement of human rights, and the criminal pursuit of perpetrators of mass atrocities. International courts and tribunals have become, in some respects, the lynchpin of the modern international legal system. The Oxford Handbook of International Adjudication uniquely brings together analysis of the legal, philosophical, ethical and political considerations brought about by these bodies. It provides an original and comprehensive understanding of the various forms of international adjudication. A series of cross-cutting chapters overview key issues in the field, both theoretical and practical, providing scholars, students, and practitioners with a detailed understanding of important legal and political influences within the international adjudicative process.